Electrochemical Immobilisation of Glucose Oxidase for the Controlled Production of H2O2 in a Biocatalytic Flow Reactor. Issue 17 (8th September 2022) - Arshi, Simin; Xiao, Xinxin; Belochapkine, Serguei; Magner, Edmond
Abstract: Electrochemical methods can be used to selectively modify the surfaces of electrodes, enabling the immobilisation of enzymes on defined areas on the surfaces of electrodes. Such selective immobilisation methods can be used to pattern catalysts on surfaces in a controlled manner. Using this approach, the selective patterning of the enzyme glucose oxidase on the electrodes was used to develop a flow reactor for the controlled delivery of the oxidant H2 O2 . GOx was immobilised on a glassy carbon electrode using polypyrrole, silica films, and diazonium linkers. The rate of production of H2 O2 and the stability of the response was dependent on the immobilisation method. GOx encapsulated in polypyrrole was selected as the optimal method of immobilisation, with a rate of production of 91±11 μM h −1 for 4 hours of continuous operation. The enzyme was subsequently immobilised on carbon rod electrodes (surface area of 5.76 cm 2 ) using a polypyrrole/Nafion® film and incorporated into a flow reactor. The rate of production of H2 O2 was 602±57 μM h −1, with 100 % retention of activity after 7 h of continuous operation, demonstrating that such a system can be used to prepare H2 O2 at continuous and stable rate for use in downstream oxidation reactions. Abstract : Electrochemical immobilisation of glucose oxidase for the controlled production of H2 O2 in a biocatalytic flow reactor is reported.